PHYTOCHEMICAL INVESTIGATION AND TOTAL ANTIOXIDANT POTENTIAL OF THE MILKY MUSHROOM, CALOCYBE INDICA Var.APK2 CULTIVATED IN TAMILNADU, INDIA - R.SUMATHY; R.KUMUTHAKALAVALLI; A.S.KRISHNAMOORTHY; VENKATESH BALAN (International Journal of Pharma and Bio Sciences, 2015)
Phytochemicals of mushrooms are nutritionally functional and a source of physiologically beneficial medicines. In the present study, crude hot water; cold water extracts of Calocybe indica was qualitatively screened for the presence of phytochemicals. Hot water extracts showed the presence of many phytochemicals like polysaccharide, phenol, flavonoids, alkaloid, terpenoid and saponin when compared to that of the cold water extract. The hot water extracts were further analysed for their antioxidant activity through in vitro studies using reducing power, DPPH, superoxide, hydroxyl, hydrogen per oxide radical scavenging, β-carotene and linoleate leaching and lipid peroxidation assays. All the assays were carried out with the concentration of extracts ranging from 20μg/ml to 100 μg/ml, all the tested assays revealed the significant antioxidant activity from 15-86%. These results provide evidence that the hot water extracts of C.indica might indeed be a potential source of natural antioxidant which could be utilized in diet to quench the free radicals produced in the body.